Trainee Awareness of US Preventive Services Task Force (USPSTF) Colorectal Cancer Screening Guidelines - Madaliene Denison; Jinman Cai; Hannah H. Roberson; Ellen Lockhart; Farrell Adkins (Journal of Cancer Education, 2026)
In 2021, the US Preventive Services Task Force (USPSTF) issued a final recommendation to lower the initial age for colorectal cancer (CRC) screening to 45 1 . At many institutions, trainees play a critical role in the implementation of CRC screening guidelines. The aim of the current study is to assess trainee awareness of recent changes to CRC screening guidelines. Trainees in surgical and non-surgical residency and fellowship programs at a single academic medical center were surveyed, in February of 2023, regarding awareness of recent changes to CRC screening guidelines. Additional information regarding trainee recommendations for various types of screening modalities and their perceptions of patient awareness was obtained. A total of 116 trainees responded to the survey, reflecting a 39% response rate. Of trainees recommending CRC screening, 75% recommended screening to be initiated at age 45, 13% at age 50, 6% at age 40, and 2% at age greater than 50. Trainee knowledge of screening guidelines came from medical school learning (70.7%) and USPSTF guidelines (82%). The most recommended screening modalities were colonoscopy (87%), fecal immunochemical testing (FIT) (31%), and fecal occult blood testing (FOBT) (15%). In comparing trainees who perform colonoscopies versus trainees from primary care specialties, there was no statistical difference between groups regarding knowledge on current screening guideline recommendations. Most trainees recommended CRC screening during their training. Unfortunately, many trainees were unaware of recent changes to CRC screening guidelines. These results revealed an important knowledge gap to be addressed among surgical and non-surgical trainees.